2016
DOI: 10.1002/ijch.201600015
|View full text |Cite
|
Sign up to set email alerts
|

On the Centenary of Emanuel Gil‐Av, Former Professor of the Weizmann Institute of Science and Pioneer of Enantioselective Chromatography

Abstract: Emanuel Gil‐Av (Zimkin) was born in 1916 and passed away in 1996. The introduction of chemical selectivity into the chromatographic separation process constitutes his main scientific contribution. This approach culminated in the first enantiomeric separation of racemic amino acids by gas chromatography on an optically active chiral stationary phase in 1966, together with Binyamin Feibush and Rosita Charles‐Sigler. Thus the year 2016 marks an important date to remember and to appreciate the invaluable achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…Additional tests involving different ratios of enantiomers in the samples being analysed or inverting the configuration of the chiral stationary phase, from L‐ to D‐isoleucine, confirmed that intermolecular interactions were different for each enantiomer, resulting in different retention times ,…”
Section: Fundamental Developments Of Chiral Stationary Phases For Gasmentioning
confidence: 92%
See 1 more Smart Citation
“…Additional tests involving different ratios of enantiomers in the samples being analysed or inverting the configuration of the chiral stationary phase, from L‐ to D‐isoleucine, confirmed that intermolecular interactions were different for each enantiomer, resulting in different retention times ,…”
Section: Fundamental Developments Of Chiral Stationary Phases For Gasmentioning
confidence: 92%
“…[37] Additional tests involving different ratios of enantiomers in the samples being analysed or inverting the configuration of the chiral stationary phase, from L-to D-isoleucine, confirmed that intermolecular interactions were different for each enantiomer, resulting in different retention times. [38,39] Eventually, it was also noticed that enantiomer separation by gas chromatography could be routinely performed through three main kinds of intermolecular interactions in chiral stationary phases (CSPs): [40] (1) separation of enantiomers of chiral amino acids via hydrogen bonding, [41,42] (2) separation of those enantiomers on chiral metal complexes via coordination of the analyte, [43,44] and (3) enantiomeric separation on cyclodextrin derivatives via selective inclusion into the cavity of the chiral cyclic oligosaccharide. [45][46][47][48]…”
Section: Fundamental Developments Of Chiral Stationary Phases For Gasmentioning
confidence: 99%
“…As early as the end of 1960th, seminal works of Gil-Av [68] and Davankov [69] have introduced long-awaited techniques for separating enantiomers and analyzing enantiomeric composition of organic compounds by means of gas and liquid chromatography, respectively. Chiral chromatography paved the way for numerous stereochemical studies.…”
Section: Origins Of Biological Homochiralitymentioning
confidence: 99%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 Reports on the 81 st Annual Meeting of the ICS, [1] and the ICS Symposium Honoring Wolf Prize Laureates K. C. Nicolaou and Stuart L. Schreiber; and Essays on Ernest Wenkert, [2] and Emanuel Gil-Av. [3,4] Several exciting features are planned for Volumes 57-58 (2017-8), including Rosarium Philosophorum on Organic Synthesis, Amyloid Aggregation, Computational Science of Inorganic Nanostructures, Charge Migration in Proteins, Iron Catalysis, Magnetic Resonance -Molecular Imaging, Total Synthesis with Gold, as well as special issues honoring the 2016 and 2017 Wolf Prize Laureates in Chemistry, titled "Advancing Science through Synthetic Chemistry and Chemical Biology" (K. C. Nicolaou and S. L. Schreiber) and "Bond Activation by Metal Complexes" (R. Bergman).…”
Section: Issue 2-3 On Porphyrins and Porphyrinoids Edited Bymentioning
confidence: 99%
“…[3,4] Several exciting features are planned for Volumes 57-58 Finally, I wish to point out that all these achievements have resulted from a group effort and dedication of many individuals, including all Guest Editors, the well-selected contributing authors and referees, members of the Editorial Board and the International Advisory Board and, in particular, the journal's Publisher, Dr. …”
mentioning
confidence: 99%